Characterizing reasons for exercise in binge-spectrum eating disorders. (December 2021) - Lampe, Elizabeth W.; Trainor, Claire; Presseller, Emily K.; Michael, Megan L.; Payne-Reichert, Adam; Juarascio, Adrienne S.; Manasse, Stephanie M.
Abstract: Although 40–60% of individuals with eating disorders (EDs) report engaging in maladaptive exercise, self-reported reasons for engaging in exercise vary. Further, no studies have examined momentary reasons for exercise and whether reasons for exercising could be both adaptive and maladaptive for any episode. Examining reasons for exercise can inform interventions which more effectively target maladaptive exercise. The current study recruited adults with binge-spectrum EDs ( N = 58, 89.2% Female) and assessed self-reported reasons for exercise using ecological momentary assessment over 7–14 days. Exercise episodes were categorized as maladaptive if the participant endorsed exercising to compensate for eating or feeling driven to exercise. On average, participants reported exercising 8 times ( SD = 8) over the 7–14 days. On average, 73% of exercise episodes were maladaptive. Participants most frequently stated exercising to control shape or weight (67.2% of episodes), feeling driven (62.9%), and exercising as part of a routine (52.9%). Participants least endorsed exercising so that they could eat more later (9.8%). Participants reported a mean of 3.6 reasons for exercising at each episode ( SD = 1.85, mode = 1.0). As hypothesized, individuals with EDs were exercising for several reasons at each exercise episode. Further, the extent to which each exercise episode is maladaptive varied between participants and even within a single participant's exercise episodes. These findings underscore the importance of research evaluating when, and for whom, exercise becomes maladaptive, as well as research examining other characteristic features of maladaptive and adaptive exercise in EDs. Highlights: Individuals with EDs may have a mix of adaptive and maladaptive exercise episodes. Individuals report adaptive and maladaptive reasons at any given exercise episode. Treatments should approach exercise flexibly, depending on patient presentation.